2020
DOI: 10.1136/ijgc-2020-002032
|View full text |Cite
|
Sign up to set email alerts
|

Management of menopausal symptoms and ovarian function preservation in women with gynecological cancer

Abstract: Gynecological cancers affect a growing number of women globally, with approximately 1.3 million women diagnosed in 2018. Menopausal symptoms are a significant health concern after treatment for gynecological cancers and may result from oncologic treatments such as premenopausal bilateral oophorectomy, ovarian failure associated with chemotherapy or radiotherapy, and anti-estrogenic effects of maintenance endocrine therapy. Additionally, with the growing availability of testing for pathogenic gene variants such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Hot flashes and sweating seem to be specific symptoms of perimenopausal onset [ 24 ]. In addition, cancer-related treatments such as surgery, radiotherapy, and chemotherapy can cause ovarian failure and further affect hormone levels, which can lead to autonomic dysfunction and cause symptoms such as spontaneous perspiration, night sweats, and hot flushes [ 25 ]. Previous studies have identified this symptom cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Hot flashes and sweating seem to be specific symptoms of perimenopausal onset [ 24 ]. In addition, cancer-related treatments such as surgery, radiotherapy, and chemotherapy can cause ovarian failure and further affect hormone levels, which can lead to autonomic dysfunction and cause symptoms such as spontaneous perspiration, night sweats, and hot flushes [ 25 ]. Previous studies have identified this symptom cluster.…”
Section: Discussionmentioning
confidence: 99%
“…This is because breast cancer is the most common female cancer, it's treatment often involves the use of agents which may induce menopausal symptoms and MHT is generally contraindicated after breast cancer. We anticipate that there will be a smaller group of patients with gynaecological cancer as MHT can often be used safely after a diagnosis of gynaecological malignancy [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, this raises concerns for its use in women on aromatase inhibitors where the goal of therapy is to lower estrogen levels as much as possible [89,90]. A dearth of data exists for gynaecological cancers [91]. Given the reassuring observational data in breast cancer survivors, it is reasonable to offer vaginal estrogen where required even in those for whom systemic MHT is not recommended in discussion with the treating oncologist.…”
Section: Management Of Urogenital Symptomsmentioning
confidence: 99%